Analisa Perhitungan Kebutuhan Tenaga Kerja Menggunakan Resource Leveling Method danWork Load Analysis - Dwi Nur Indah Sari; Renanda Nia Rachmadita; Fitri Hardiyanti (Proceedings Conference On Design Manufacture Engineering And Its Application, 2019)
PT. BBI (Boma Bisma Indra) is one of the manufacturing companies, working based on orders from consumers, which starts from the design process (Engineering To Order). The products produced include pressure vessels, condensers, cranes and heat exchangers. The problem that arises is that production has been experiencing delays, one of which is due to labor. Could be because the composition of the number of workers is not right or the workload is not yet suitable. To find out these problems, resource leveling methods are used to optimize / evenly distribute the number of human resources used so that there is no significant difference from the number of workers in each activity, and avoid the possibility of excess labor. In its application this method can use the PDM (Precedence Diagram Method) method. After the leveling of human resources (resource leveling) will then be performed calculations of human resource needs using work load analysis to determine the workload on each work activity. The results showed a labor of 1 person marking, 2 people leave, 2 people drilling, 2 people assembly, and finishing 6 people. With the existing workload produced more labor, namely marking 1 person, cutting 5 people, drilling 3 people, assembling 6 people, and finishing 21 people.